Análisis de los factores claves de la estrategia de marketing digital para aumentar las ventas de la marca Pretz - Pretell Gamarra, Maria Jimena (2020)
The present research proposes to demonstrate the increase in sales of the Pretz brand from the development of digital marketing strategies such as the appropriate use of branded content and an effective after-sales service to retain and attract more customers. The research uses a mixed method with 10 surveys of digital marketing and after-sales service specialists from the stores where Pretz operates in Lima (Peru), and an interview with the brand manager. Research shows that the combined application of the two proposed improvements generates a 30% increase in new customers attracted.